2011
DOI: 10.1016/j.foodcont.2011.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Unintentionally produced dioxin-like polychlorinated biphenyls during cooking

Abstract: a b s t r a c tThe formation and distribution of dioxin-like polychlorinated biphenyls (dl-PCBs) during cooking was investigated. Concentrations of dl-PCBs in liquid residues, cooked beef, and oil fumes generated during heating were determined by isotope dilution HRGC/HRMS. Although the levels of dl-PCBs in well-done beef were lower compared with those of raw beef, relatively high concentrations of dl-PCBs were detected in the oil fumes produced during heating. This suggests that dl-PCBs in raw beef may have v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The experimental system and heating procedures used have been described previously by Dong et al (2011, 2013)1618. The tetra- to octa-chlorinated PCDD/F homologue groups and 17 individual 2,3,7,8-substituted PCDD/F congeners in the smoke and the residues were analysed following the U.S. Environmental Protection Agency method 1613.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental system and heating procedures used have been described previously by Dong et al (2011, 2013)1618. The tetra- to octa-chlorinated PCDD/F homologue groups and 17 individual 2,3,7,8-substituted PCDD/F congeners in the smoke and the residues were analysed following the U.S. Environmental Protection Agency method 1613.…”
Section: Methodsmentioning
confidence: 99%
“…Rahn & Yaylayan (2010) reported that the thermal degradation of sucralose at 250°C resulted in the generation of toxic chloropropanols15. Our previous studies showed that highly toxic polychlorinated aromatic compounds, such as polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs), dioxin-like polychlorinated biphenyls, and polychlorinated naphthalenes, could be generated during the heating of foodstuffs in the presence of sucralose161718. It still remains unclear whether these highly toxic compounds could be produced when pure sucralose is heated, and the formation mechanisms for these compounds have not yet been elucidated.…”
mentioning
confidence: 99%
“…A schematic representation of the stainless steel system used in the current study has been provided elsewhere by Dong, Wu, Liu, Zhang, and Zheng (2011). In each experiment, 50 g of cooking oil (peanut oil or olive oil) and 5 g of sucralose or sodium chloride were poured into a stainless steel bowl.…”
Section: Cooking Process and Samplingmentioning
confidence: 99%
“…Analyses of the 17 toxic PCDD/F and 12 dl-PCB congeners were carried out according to the US EPA Methods 1613 and 1668A, respectively. Sample extraction, cleanup and instrument analysis of the PCDD/Fs and dl-PCBs were conducted according to the methods of Dong et al (2011).…”
mentioning
confidence: 99%
“…The effect of cooking on the levels of PBTs in foodstuffs is varying depending on the type of food and probably on the type of cooking process. [80][81][82] Indubitably, this field requires further studying, with specific input on how each cooking process influences each vegetable category and each chemical class.…”
Section: Effect Of Cooking On Vegetables Contamination From Pbtsmentioning
confidence: 99%